2021
DOI: 10.3390/foods10102495
|View full text |Cite
|
Sign up to set email alerts
|

Low Acrylamide Flatbreads from Colored Corn and Other Flours

Abstract: Dietary acrylamide formed during baking and frying of plant-based foods such as bread and other cereal products, coffee, fried potatoes, and olives is reported to induce genotoxic, carcinogenic, neurotoxic, and antifertility properties in vivo, suggesting the need to keep the acrylamide content low with respect to widely consumed heat-processed food including flatbreads. Due to the fact that pigmented corn flours contain biologically active and health-promoting phenolic and anthocyanin compounds, the objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Discovered in 2002 in thermally processed foods, acrylamide (prop-2-enamide) is a white, odorless, and water-soluble powder . It is considered a neuro- and reproductive toxin as well as a group 2A or probable carcinogen. ,, This classification indicates that, although limited evidence of carcinogenicity was found in humans, concrete evidence was found in animals…”
Section: Introductionmentioning
confidence: 99%
“…Discovered in 2002 in thermally processed foods, acrylamide (prop-2-enamide) is a white, odorless, and water-soluble powder . It is considered a neuro- and reproductive toxin as well as a group 2A or probable carcinogen. ,, This classification indicates that, although limited evidence of carcinogenicity was found in humans, concrete evidence was found in animals…”
Section: Introductionmentioning
confidence: 99%
“…As part of efforts to create new functional foods that have the potential to ameliorate and treat human diseases, we reported that edible algae (Ecklonia cava) bioprocessed (fermented) in culture with shiitake mushroom mycelia was effective in neutralizing multiple biomarkers associated with allergic asthma in mice [1]. We also published a series of studies on the preparation of experimental, mostly gluten-free, flatbreads with other health benefits, as well as with a low content of the heat-induced toxin acrylamide formed during the baking process [2][3][4][5]. Because edible E. cava algae contain multiple antioxidative polyphenolic compounds that are reported to be safe to consume (discussed below) and to have multiple health benefits in vitro and in vivo (highlighted below), and colored (pigmented) corn flours also contain different health-promoting phenolic compounds and anthocyanins (highlighted below), expectations are that the combination of biologically active compounds present in colored corn flour and the alga might act additively or synergistically against human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…gValues with different superscript letters differ significantly (p ≤0.05), n=3. Colored corn data from[5].…”
mentioning
confidence: 99%
“…As part of this effort, we previously devised improved thermal processing conditions to reduce acrylamide formation in canned black ripe olives [ 8 ], prepared a set of gluten-free, low-acrylamide commercial and experimental flatbreads [ 9 ], and determined the effects of adding fruit and vegetable peels and mushroom powders to gluten-free experimental flatbreads on their acrylamide contents [ 10 ]. We also reported in this journal on low acrylamide flatbreads prepared from colored corn and other flours [ 11 ].…”
Section: Introductionmentioning
confidence: 99%